A Study of Linguistic Expressions Denoting Colors in 19th-Century English Literature - Lê Thị Hồng Nhung (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
To understand the linguistic trends: Understand the overall linguistic trends and structures in the use of colors in 19th-century English Literature and their impact on narrative techniques; To unravel sociocultural context: Examine the socio-cultural construct of the period through the use of color expressions and theirassociations.